2021
DOI: 10.3390/ijms222111870
|View full text |Cite
|
Sign up to set email alerts
|

RNA Modifications and RNA Metabolism in Neurological Disease Pathogenesis

Abstract: The intrinsic cellular heterogeneity and molecular complexity of the mammalian nervous system relies substantially on the dynamic nature and spatiotemporal patterning of gene expression. These features of gene expression are achieved in part through mechanisms involving various epigenetic processes such as DNA methylation, post-translational histone modifications, and non-coding RNA activity, amongst others. In concert, another regulatory layer by which RNA bases and sugar residues are chemically modified enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 217 publications
(244 reference statements)
0
24
0
Order By: Relevance
“…Recently, chemical modifications of RNA (a.k.a. epitranscriptomics) emerged as a novel layer of gene expression regulation in healthy tissues (e.g., brain), as well as in several pathologies such as neurodegenerative diseases 7 and cancer. 8 , 9 In particular, we and others associated several chemical marks with cancer evolution, adaptation, as well as the response to conventional therapy.…”
mentioning
confidence: 99%
“…Recently, chemical modifications of RNA (a.k.a. epitranscriptomics) emerged as a novel layer of gene expression regulation in healthy tissues (e.g., brain), as well as in several pathologies such as neurodegenerative diseases 7 and cancer. 8 , 9 In particular, we and others associated several chemical marks with cancer evolution, adaptation, as well as the response to conventional therapy.…”
mentioning
confidence: 99%
“…RT-PCR demonstrated that TDP43C-spl was expressed in human spinal cord, brain tissue and DRG. This may be explained by the fact that, like other alternatively spliced genes, the differential expression of the various TDP-43 isoforms may be regulated by the interplay of cis elements and trans factors that exhibit cell type specificities (Chatterjee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, m6A modifications have been shown to play a role in different processes including learning memory, neurogenesis, and axon regeneration. The dysregulation of m6A pathways has been implicated in the onset of neurological diseases including AD, where m6A modifications at the 3′-UTR of mRNAs alters the translation of transcripts linked to age-related disease phenotypes [ 20 ]. In accordance, recent evidence showed a progressive m6A increase concomitantly with AD severity in human brains.…”
Section: Translation Impairment In Neurodegenerationmentioning
confidence: 99%